ICT skills, and benefits of teaching and learning animal science with blended learning at colleges of education in Ghana - Dzakpasu Edem Prince; Christopher Dewodo; Pascal Benson Atiglah (Journal of Education and Learning (EduLearn), 2020)
Animal science is an essential curriculum in animal husbandry and veterinary professional education. This study delved into the use of ICT in teaching animal science using blended learning and the benefits of blended learning for teachers and students. The study utilized a descriptive survey design. The target population consisted of animal science students and teachers selected colleges of education in the Volta region. The population of Agric science students was 100, and the Agric science tutors in the three colleges were 20. With the use of Yamane formula, the sample size was 80 and 19 respectively for students and the teachers. The fundamental instrument for data collection was questionnaires. Four and five scaled Likert like tests were designed to elicit information on the level of ICT skill of teachers and their students, and on benefits of blended learning to teachers and students respectively. The information gathered was analyzed using SPSS version 21 and the hypotheses were tested using Analysis of Covariance. The result established that both teachers and students of animal science department in the Colleges that participated in the study, are skilled in ICT and that both teachers and students benefited from using blended learning model in teaching animal science in colleges of education in Ghana. It was also discovered from hypothesis tested that no significant difference existed between the ICT skill level of teachers and students, and no significant difference also existed between the level of benefit derived from blended learning by both teachers and students. It was concluded that both teachers and students of animal science in the colleges of education in Ghana benefited from blended learning model because they are skilled in ICT. Hence, it was recommended that teachers and students must be well trained to acquire sufficient ICT skills in the usage of basic ICT applications in order to obtain the full benefits of the blended learning model.